2018
DOI: 10.1007/s00104-018-0636-z
|View full text |Cite
|
Sign up to set email alerts
|

CA19-9 beim intrahepatischen Cholangiokarzinom

Abstract: Preoperatively assessed CA19-9 levels >1000 U/ml are a strong negative prognostic factor of postoperative disease-specific survival in patients suffering from intrahepatic cholangiocarcinoma. Future studies are necessary to evaluate if patients with highly elevated CA19-9 serum levels should be considered for modified treatment strategies (e. g. neoadjuvant or adjuvant therapy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As we all know, the content of serum tumor markers will change with the continuous development of the disease. The detection of serum tumor markers helps to detect abnormalities in the body as soon as possible and improve the early diagnosis rate of tumors [ 26 ]. AFP and CA199 are commonly used tumor markers for the diagnosis of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, the content of serum tumor markers will change with the continuous development of the disease. The detection of serum tumor markers helps to detect abnormalities in the body as soon as possible and improve the early diagnosis rate of tumors [ 26 ]. AFP and CA199 are commonly used tumor markers for the diagnosis of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Domestic studies suggest that elevated CA19-9 can be used as an independent factor in cholangiocarcinoma, but most studies are based on operable patients. [7,[30][31][32][33][34] Domestic scholars believe that the survival rate of preoperative CA19-9 level < 150 U/mL is significantly better than that of patients with high CA19-9 level. [35] Heimbach et al [36] found that CA 19-9 > 100 U/mL can be used as a predictor of recurrence in liver transplant patients by performing orthotopic liver transplantation in 65 patients with HCCA who cannot undergo surgical resection.…”
Section: Discussionmentioning
confidence: 99%